AN EMPIRICAL ANALYSIS OF FUNDS’ ALTERNATIVE MEASURES IN THE DRAWDOWN RISK MEASURE (DRM) FRAMEWORK - Tavakoli Baghdadabad, Mohammad Reza; Mat Nor, Fauzias; Ibrahim, Izani (Journal of Advanced Studies in Finance, 2011)
This paper aims to evaluate the risk-adjusted performance of Malaysian mutual funds using the modified performance evaluation ratios by the drawdown risk measure (DRM) based on modern portfolio theory, and to represent the results in a manner which is easily understood by the average investors and portfolio managers. It evaluates the performance of 91 Malaysian mutual funds using risk-adjusted returns over the 2000-2011. The DRM, as a different measure from downside risk, is applied to improve seven risk-adjusted performance measures of Sharpe, Treynor, M-squared, Jensen’s alpha, information ratio (IR), MSR, and FPI. It proposes a new single-factor model to estimate the drawdown beta and alpha in the DRM framework. This paper is the first study to estimate a new regression model in the DRM framework to evaluate the performance of Malaysian mutual funds. The evidence shows that replacement framework in terms of MDB, the drawdown beta, and the drawdown CAPM can be replaced to the conventional frameworks in terms of MVB, beta, and the CAPM and also MSB, downside beta, and D-CAPM to modify seven performance evaluation measures of Malaysian mutual funds.